Conflictive uses of coastal areas: A case study in a southern European coastal lagoon (Ria de Alvor, Portugal). (November 2016) - Mateus, M.; Almeida, D.; Simonson, W.; Felgueiras, M.; Banza, P.; Batty, L.
Abstract: Estuaries and coastal lagoons are naturally stressed and highly variable ecosystems, and are also frequently exposed to strong anthropogenic pressures. Such pressures can be particularly pronounced in small systems such as the Ria de Alvor, a small tidal lagoon in southern Portugal. The Ria de Alvor is a priority area for conservation, being a RAMSAR wetland of international importance since 1996 and is part of the European Ecological Network, Natura 2000 . Nevertheless, intensive anthropogenic uses exert increasing pressures on its ecological features, causing stresses and challenges which are addressed in this paper. The resources that the Ria de Alvor provides are both marine and terrestrial in nature, and are subject to various kinds of exploitation. Urban, industrial and tourist developments, as well as agriculture and animal rearing, have resulted in habitat loss and change, altered morphology and hydrodynamics, and the discharge of effluents into the system. This paper reviews the key features and issues existing in the Ria and highlights the need for more research into this and other small estuaries and their management. Highlights: Anthropogenic pressures are particularly pronounced in small coastal systems. We study such a system for which there is only a few studies made to date. We review key features and issues in the management of the Ria de Alvor. Our study points to the need for more research into this and other small estuaries.